Coefficient conditions for the asymptotic stability of solutions of systems of linear difference equations with continuous time and delay - Kaiser, C.; Korenevsky, D. G. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish sufficient algebraic coefficient conditions for the asymptotic stability of solutions of systems of linear difference equations with continuous time and delay in the case of a rational correlation between delays. We use (n 2 + m)-parameter Lyapunov functions (n is the dimension of the system of equations and m is the number of delays).